2019
DOI: 10.1089/ped.2018.0911
|View full text |Cite
|
Sign up to set email alerts
|

Successful Use of Pulmonary Cryotherapy for Tracheobronchial Thrombus Extraction and Recanalization of the Tracheobronchial Tree During a Pediatric Venovenous Extracorporeal Membrane Oxygenation Run

Abstract: Impacted pediatric tracheobronchial thrombus is an uncommon diagnosis. There are no clearly proven therapeutic options for airway casts due to a similar process, plastic bronchitis. Cryotherapy, specifically cryoextraction, has shown potential as a therapeutic option in adults with tracheobronchial thrombus and cast. We describe the novel application of this method in a complex pediatric patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 8 publications
1
25
0
Order By: Relevance
“…1 Bronchoscopic cryoextraction (i.e., using cryotherapy to remove material en bloc from the airway) has shown promise for the removal of large mucus plugs, obstructive thrombi, and foreign bodies in children. 2,3 Although there are no reports of serious complications related to cryoextraction in children, the risk of hemorrhage is likely enhanced in coagulopathic patients, including those receiving anticoagulation for extracorporeal membrane oxygenation (ECMO) support. Because the bronchoscope and cryoprobe must be removed in tandem to extricate foreign material, there is a period of time when visualization of the airway is lost.…”
mentioning
confidence: 99%
“…1 Bronchoscopic cryoextraction (i.e., using cryotherapy to remove material en bloc from the airway) has shown promise for the removal of large mucus plugs, obstructive thrombi, and foreign bodies in children. 2,3 Although there are no reports of serious complications related to cryoextraction in children, the risk of hemorrhage is likely enhanced in coagulopathic patients, including those receiving anticoagulation for extracorporeal membrane oxygenation (ECMO) support. Because the bronchoscope and cryoprobe must be removed in tandem to extricate foreign material, there is a period of time when visualization of the airway is lost.…”
mentioning
confidence: 99%
“…Bronchoscopic cryoextraction (i.e. using cryotherapy to remove material en bloc from the airway) has shown promise for the removal of large mucus plugs, obstructive thrombi, and foreign bodies in children [2,3]. Although there are no reports of serious complications related to cryoextraction in children, the risk of hemorrhage is likely enhanced in coagulopathic patients, including those receiving anticoagulation for extracorporeal membrane oxygenation (ECMO) support.…”
Section: Two-bronchoscope Technique For Cryoextraction: An Alternativ...mentioning
confidence: 99%
“…Ryne Simpson MD 1,2 , Isabel Virella-Lowell MD 1,2 , Hitesh Batra MD 3,4 , Guillermo Beltran Ale MD The authors declare they have no relevant financial interests.…”
Section: Authorsmentioning
confidence: 99%
“…The success, feasibility, and utility of airway cryotherapy via FB has been reported in children and adults for a variety of indications including endobronchial cryobiopsy, recanalization of obstructed bronchial stents, alleviating airway obstruction due to granulation tissue, mucus plugs, endobronchial tumors, endobronchial thrombi, plastic bronchitis, and removal of aspirated foreign bodies 3,5–13 . However, only a few studies have reported on using cryotherapy via FB in children 3,7,8,10–13 .…”
Section: Introductionmentioning
confidence: 99%